Abundance - Klein, Ezra, 1984-; Thompson, Derek, 1986- (Avid Reader Press, an imprint of Simon & Schuster, 2025)
This book discusses the history of the twenty-first century as a story of unaffordability and shortage in America. It highlights the national housing crisis, labor shortages due to limited immigration, insufficient clean-energy infrastructure, and delayed, over-budget public projects. The author argues that the root cause of these problems is a lack of sufficient building and proactive planning over the decades. Many of today's issues stem from past policies and regulations that, while intended to address issues of the 1970s, now hinder progress in areas like urban density and green energy. The book stresses that while we have become more aware of these problems, our ability to solve them has diminished. The book proposes that both liberals and conservatives need to recognize when government is failing or needed, and advocates for a politics of abundance--building solutions for the future, rather than adhering to past approaches focused on scarcity. This approach aims to address current challenges and the growing dissatisfaction with the status quo.